Descrição de novos cariótipos em espécies de sciuridae, dasyproctidae e erethizontidae com discussão da evolução cromossômica nos caviomorpha - Lima, José Fernando de Sousa (1993)
Cytogenetic studies were made on two species of Eretizhontidae and Dasyproctidae (Rodentia:Caviomorpha), and two of Sciuridae family (Rodentia:Sciuromorpha). The staining cytogenetics techniques consisted of conventional Giemsa, G -, C - G and NOR- Banding. Coendou prebensilis showed a karyotype (2n=74 and a FN=78) with 3 pairs of biarmed chromosomes and a metacentric X c-banded on the short arm. The NOR-band occured on a medium sized biarmed chromosome. Spbiggurus insidiosus showded a karyotype (2n=62 and a FN=78) with 9 biarmed chromosomes and a submetacentric X chromosome. The Y chromosome exhibited na heterochromatic region in its middle part. The NOR-band occurred in a uniarmed chromosome. Dasyprocta aguti (2n=64and fn=122) showed 30 biarmed chromosome pairs and the NOR-band occurred in a large unimarmed chromosome. Dasyprocta fuliginosa showed a 2n=64 and a fn=122 caryotype. As the former species, it showed 30 biarmed chromosome pairs and the NOR-band on the single acrocentric chromosome. The karyotype is similar to that described for of D. aguti. Sciurus aestuans ( 2n=40 and NF=76) shows 19 biarmed chromosome pairs and a secondary constriction on the first chromosome pair. The C band is pericentromeric, as usual. The sexual chromosomes were not identified. Sciurus spadiceus (2n=40 and FN=76) showed 19 biarmed chromosome pairs. The X chromosome is a medium sized subtelocentric and the Y is a medium sized acrocentric. The karyotypic pattern within Sciurus genus is quite uniform. From karyological point of view the Erethizontidae may be considered as a distinct group of caviomorpha. The ancestral karyotype for the family may be close to 2n=74, and FN=78 as observed in Coendou prebensilis. Although the secondary constriction is missing, both studied species showed NOR-bands. Among the caviomorphs a second group based on chromosome affinity may be recognized; the Dasyproctidae, Chinchillidae, Caviidae and Abrocomidae families. The ancestral diploid number of this second group could be 2n=64 since most of the member share this chromosome number. The mecanism involved on the caviomorph karyotype evolution may be of the “Robertsonian” type, fusion/ fission, and also pericentric inversions. Several hypotheses were assessed to explain the karyotype evolution in the studied families, based on the above mentioned rearrangement mechanisms. The genus Sciurus showed high karyotype stability.The Brazilian species agree in diploid number with the Northern Hemisphere species.